1976
DOI: 10.1149/1.2132919
|View full text |Cite
|
Sign up to set email alerts
|

Emitter Dip Effect by Low Temperature Heat‐Treatment of Arsenic‐Diffused Layer

Abstract: When arsenic is used as the emitter diffusant in a n-p-n silicon transistor, it is well known that the emitter dip effect is not observed. However, it was found that the diffusion of boron underneath the arsenic emitter was accelerated during heat-treatment at 500~176This phenomenon is related to abnormal behavior of arsenic in silicon. The diffusion of arsenic is enhanced by such treatment. The anomalous diffusion of arsenic depends on treatment time, and is remarkable in the beginning of the treatment. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Fair et al, have shown that this effect increases the diffusivity at 600 °C by 4 orders of magnitude relative to the value extrapolated from high temperatures; they have also shown that this enhancement will be even larger at lower temperatures. H. Shibayam et al have reported on boron and arsenic diffusivities reaching values of ∼ 1 × 10 −20 m 2 s −1 in the temperature range of 500−800 °C and with no sign for temperature dependence. They associated this enhancement to a generation of excess vacancies at low temperatures.…”
mentioning
confidence: 99%
“…Fair et al, have shown that this effect increases the diffusivity at 600 °C by 4 orders of magnitude relative to the value extrapolated from high temperatures; they have also shown that this enhancement will be even larger at lower temperatures. H. Shibayam et al have reported on boron and arsenic diffusivities reaching values of ∼ 1 × 10 −20 m 2 s −1 in the temperature range of 500−800 °C and with no sign for temperature dependence. They associated this enhancement to a generation of excess vacancies at low temperatures.…”
mentioning
confidence: 99%
“…SIMS profiles were determined with the CAMECA IMS 300 using a 5. 5 As: 10 ~8 em-~ 60 keY, 24 rain 990~ Ni mary beam. Oxygen gas was introduced into the sample chamber at a pressure of about 3 X 10-~ Torr, except for one arsenic profile, which was measured in the 10 -7 Torr residual vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown (Fair and Tsai 1977) that this effect increases the diffusivity at 600ºC by four orders of magnitude relative to the value extrapolated from high temperatures; they have also shown that this enhancement will be even larger at lower temperatures. It was reported (Shibayama, Masaki et al 1976) that Boron and Arsenic diffusivities can reach values of ~ 1x10 -20 m 2 s -1 in the temperature range of 500-800ºC and with no sign for temperature dependence. They associated this enhancement to a generation of excess vacancies at low temperatures.…”
mentioning
confidence: 97%